Gambaran Diagnosis Keperawatan Pada Pasien Diabetes Melitus di Rumah Sakit Umum Daerah Tugurejo Semarang - Oksiati Khoirunnisa; Muhamad Rofi’i; Puji Hastuti (Jurnal Ners, 2023)
DM (Diabetes Mellitus) is a metabolic disorder characterized by insulin hormone deficiency. Patients with DM exhibit various signs and symptoms, which serve as the basis for nursing diagnoses by nurses. This study aims to describe nursing diagnoses in DM patients at Tugurejo Hospital in Semarang. The research design employed was quantitative research using a survey analysis approach of medical record documents. The sample consisted of 112 medical record documents of DM patients who were hospitalized at Tugurejo Hospital in Semarang from October to December 2022. Data were analyzed using univariate analysis (descriptive analysis) with frequency distribution. Data were collected using a nursing diagnosis checklist that had been adapted to the Indonesian Standard Classification of Diseases. The results showed that the majority of DM patients were aged 45-60 years (54%), and the majority were female (61%). The most frequently occurring nursing diagnoses in DM patients were acute pain (46.4%), unstable blood glucose levels (45.5%), and impaired skin/tissue integrity (22%). The other frequently occurring nursing diagnosis was nausea (16%). The majority of nursing diagnoses were actual nursing diagnoses. Nurses and hospitals are expected to meet the basic needs of DM patients, especially in addressing acute pain issues.